Signature of circulating small non-coding RNAs during early fracture healing in mice - Bourgery Matthieu; Ekholm Erika; Hiltunen Ari; Heino Terhi J; Pursiheimo Juha-Pekka; Bendre Ameya; Yatkin Emrah; Laitala Tiina; Määttä Jorma; Säämänen Anna-Marja (Elsevier, 2025)
Fracture healing is a complex process with multiple overlapping metabolic and differentiation phases. Small non-coding RNAs are involved in the regulation of fracture healing and their presence in circulation is under current interest due to their obvious value as potential biomarkers. Circulating microRNAs (miRNAs) have been characterized to some extent but the current knowledge on tRNA-derived small RNA fragments (tsRNAs) is relatively scarce, especially in circulation.
In this study, the spectrum of circulating miRNAs and tsRNAs was analysed by next generation sequencing to show their differential expression during fracture healing in vivo. Analysed tsRNA fragments included stress-induced translation interfering tRNA fragments (tiRNAs or tRNA halves) and internal tRNA fragments (i-tRF), within the size range of 28–36 bp. To unveil the expression of these non-coding RNAs, genome-wide analysis was performed on two months old C57BL/6 mice on days 1, 5, 7, 10, and 14 (D1, D5, D7, D10, and D14) after a closed tibial fracture.
Valine isoacceptor tRNA-derived Val-AAC 5′end and Val-CAC 5′end fragments were the major types of 5′end tiRNAs in circulation, comprising about 65 % of the total counts. Their expression was not affected by fracture. After a fracture, the levels of two 5′end tiRNAs Lys-TTT 5′ and Lys-CTT 5′ were decreased and His-GTG 5′ was increased through D1-D14. The level of miR-451a was decreased on the first post-fracture day (D1), whereas miR-328-3p, miR-133a-3p, miR-375-3p, miR-423-5p, and miR-150-5p were increased post-fracture. These data provide evidence on how fracture healing could provoke systemic metabolic effects and further pinpoint the potential of small non-coding RNAs as biomarkers for tissue regeneration.